Application Prospect of High Strength Aluminum Alloy in Transmission Tower. (September 2020) - Hu, Xiaoguang; Lin, Yinhe; Cui, Zhijie; Xing, Haijun; Zhu, Binrong
Abstract: Transmission Towers are usually made of steel and protected from corrosion by hot dip galvanizing. This paper explores the application of high strength aluminum alloy to solve the problems of atmospheric corrosion of transmission tower in coastal area and heavy industry pollution area, sand erosion of zinc coating of transmission tower in strong wind sand area, and transportation difficulty in rugged mountain area. Compared with the traditional steel tower, the design and development of high-strength Aluminum Alloy transmission tower has remarkable characteristics. First, the high-strength Aluminum Alloy transmission tower does not need the traditional hot-dip galvanizing process of steel, which can reduce the pollution to the atmosphere and soil environment; Second, the density of Aluminum Alloy material is 1/3 of that of steel, which can reduce the difficulty of construction and reduce transport costs; third, high-strength Aluminum Alloy has good corrosion resistance, and there is no need for routine antiseptic maintenance as steel tower. The application of high strength aluminum alloy transmission tower in area with severe atmospheric corrosion, strong wind sand and mountainous area has high engineering application value.